Screening of Zingiberaceae extracts for antimicrobial and antioxidant activities - Mohamad, Habsah; Amran, Mugahed; Mohamed Mackeen, Muhammad Mukram; Lajis, Nordin; Kikuzaki, Hiroe; Nakatani, Nobuji; A. Rahman, A.; Ghafar; Ali, Abdul Manaf (Elsevier, 2000)
Dichloromethane and methanol extracts of 13 Zingiberaceae species from the Alpinia, Costus and Zingiber genera were screened for antimicrobial and antioxidant activities. The antimicrobial activity of most of the extracts was antibacterial with only the methanol extract of Costus discolor showing very potent antifungal activity against only Aspergillus ochraceous (MID, 15.6 μg per disc). All the extracts showed strong antioxidant activity comparable with or higher that of α-tocopherol.